HUMAN CAPITAL DEVELOPMENT POLICY IN UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2024)
This article provides a comprehensive overview of the human capital development policy in Uzbekistan, which is a cornerstone of the nation’s socio-economic transformation. It discusses the strategic initiatives and programs introduced by the government to foster an educated and skilled workforce, essential for advancing towards a competitive, knowledge-based economy. The article highlights key areas of focus, including educational reforms that aim to enhance the quality of primary, secondary, and higher education. It delves into vocational and technical training initiatives designed to address the skills gap in various sectors, aligning educational outcomes with labor market needs. Additionally, the importance of lifelong learning and continuous professional development is emphasized as a means to adapt to the evolving economic landscape. Moreover, the article examines the interplay between human capital and health, asserting that improvements in healthcare access and quality are integral to developing a productive workforce. The analysis underscores the significance of integrated policies that address both education and health as crucial elements of human capital development. The challenges and barriers to effective implementation of these policies are also addressed, including issues related to resource allocation, regional inequalities, and the need for collaborative efforts between government, private sector, and civil society. The article concludes by affirming that sustained investment in human capital is vital for achieving Uzbekistan's development goals and ensuring long-term economic growth.